OPPORTUNITIES OF ACTIVE ARCHITECTURE IN DESIGNING AN INFORMATION SYSTEM FOR AUTOMATIC CHECKING OF TASKS - Madina Ulfatjonovna Mahkamova (Web of Journals Publishing, 2024)
Pedagogical software tools focused on traditional and interactive methods, i.e. passive architecture, have been used for independent education and practical training of students. But it is recommended to use an active architecture when checking assignments. Developed and designed models, client-server, ER diagrams, production models, and part algorithms to verify independent learning and practical training assignments.
Keywords: database, self-learning, architecture, CASE tasks, production models, criteria.